Excess ventilation and chemosensitivity in patients with inefficient ventilation and chronic coronary syndrome or heart failure: a case–control study - Prisca Eser; Dominic Käesermann; Pietro Calamai; Anja Kalberer; Laura Stütz; Sarina Huber; James Duffin; Matthias Wilhelm (Frontiers in Physiology)
BackgroundIn patients with chronic coronary syndromes (CCS), increased ventilation/carbon dioxide production (V̇E/V̇CO2) slope has been found to predict disease progression and mortality, similarly to patients with heart failure (HF); however, increased chemosensitivity, a well-established predictor for mortality in patients with HF, has rarely been assessed in patients with CCS.MethodPatients with CCS, HF with reduced ejection fraction (EF < 50%), healthy controls (45+ years), and young healthy adults (<35 years) were recruited. For patients, a V̇E/V̇CO2 slope ≥36 was an inclusion criterion. The Duffin rebreathing method was used to determine the resting end-expiratory partial pressure of carbon dioxide (PETCO2), ventilatory recruitment threshold (VRT), and slope (sensitivity) during a hyperoxic (150 mmHg O2) and hypoxic (50 mmHg O2) rebreathing test to determine the central and peripheral chemosensitivity.ResultsIn patients with CCS, HF, controls, and young healthy adults, median V̇E/V̇CO2 slopes were 40.2, 41.3, 30.5, and 28.0, respectively. Both patient groups had similarly reduced hyperoxic VRT (at PETCO2 42.1 and 43.2 mmHg) compared to 46.0 and 48.8 mmHg in the control and young healthy adults. Neither hypoxic VRT nor hyper- or hypoxic slopes were significantly different in patients compared to controls. Both patient groups had lower resting PETCO2 than controls, but only patients with HF had increased breathing frequency and rapid shallow breathing at rest.ConclusionIn patients with HF and/or CCS and excess ventilation, central chemoreflex VRT was reduced independently of the presence of HF. Low VRTs were related to resting excess ventilation in patients with CCS or HF; however, rapid shallow breathing at peak exercise was present only in patients with HF.Clinical trial registration numberNCT05057884.